Π-Expanded pyrazinoporphyrins for photocatalysis: How many rings are required?. (February 2023) - Shremzer, Ekaterina S.; Polivanovskaia, Daria A.; Birin, Kirill P.; Gorbunova, Yulia G.; Tsivadze, Aslan Yu
Abstract: A series of π-expanded pyrazinoporphyrins were successfully prepared and tested as sensitizers for photocatalytic aerobic sulfides oxidation. 2, 3-Diaminoporphyrin derivative was used as a key intermediate for the preparation of porphyrins fused with naphtho-, phenanthrene-, phenanthroline- and acenaphthoquinone fragments and the structures of the obtained compounds were proved by detailed analysis of NMR. The peculiarities and limitations of the condensation of diaminoporphyrin with a set of corresponding aromatic quinones were investigated. Gradual bathochromic shift of absorption bands was observed in the series of the prepared compounds, correlating with the gradual expansion of the macrocycle aromatic system. The photostability of the obtained photosensitizers was tested prior to their application as photocatalysts. The photocatalytic performance of the obtained π-expanded pyrazinoporphyrins was investigated in the aerobic oxidation of thioanisole and revealed the increase of the activity with the expansion of the π-system of the molecule. Complete conversion of the substrate and over 98% selectivity was achieved with 10 −2 mol% catalyst loading, that correspond to turnover number (TON) ca . 10, 000. The maximal TON = 89, 000 could be reached with 10 −3 mol% catalyst loading. The measurements of the singlet oxygen generation quantum yields along with the DFT analysis of perturbation of the molecular orbitals of the photosensitizers was performed. The latter analysis revealed the presence of orbitals with predominant localization either at porphyrin macrocycle or at peripheral polyaromatic part of the molecule, allowing to expect charge separation upon photoexcitation. Graphical abstract: Image 1 Highlights: General approach to π-expanded pyrazinoporphyrins is demonstrated. π-Expansion of pyrazinoporphyrins allows enhancement of photocatalytic performance. Over 98% selectivity is achieved in photocatalytic sulfoxidation. Extremely low loadings of photocatalysts allow achieving of high TONs. π-Expansion of pyrazinoporphyrins alters their photostability.